To the realization of perfect helplessness - Lewis, Robin Coste (Alfred A. Knopf, 2022)
"From the National-Book-Award-winning poet who changed the way we see the Black female figure, a continuation of that journey in a genre-bending coming together of poem and photography, toward a new definition of human migration. Twenty-five years ago, after her grandmother's death, Robin Coste Lewis discovered a stunning collection of photographs under her bed. The poetry that she marries to these vivid daily images of 20th-century Black joy and survival ("I am trying / to make the gods / happy,"; "I am trying / to make the dead / clap and shout") stands forth as an alternative to the usual way we frame the story of "race" and "the great migration"-as she puts it, "all those other clever ways we've created not to talk about Black culture." Communing with the engaging photographic vernacular of her particular family, to be revealed on black pages with white type, Lewis quite literally reverses all expectations. In her words, she makes a private documentary public; she tries to "get out of my own historical and national aesthetic habits (e.g., never cue a gospel choir; never cue a noble slave; always worship darkness)" and to liberate the photographs of Black life "from colonial nostalgia-to reframe them with a kind of exalted existentialism. Not surprisingly, it was poetry that brought the keys.""--